Identification of predictor factors of post-traumatic growth (PTG) post COVID-19 Pandemic: A systematic literature review - Hayati, Elli Nur; Nuradilah; Urbayatun, Siti (Insight: Jurnal Ilmiah Psikologi, 2024)
COVID-19 pandemic left so much unknown and unexplored knowledge in the field of Positive Psychology. This systematic literature review (SLR) aims to identify the factors that can predict posttraumatic growth after the traumatic exposure of COVID-19 pandemic. This SLR employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, with article selection criteria formulated using the Populations, Exposure, Outcomes, and Study Design (PEOS) framework. This SLR found that the only consistent external predictive factor for PTG is social support, while the consistent internal factors from inside the individual are self-efficacy, resilience, adaptive coping, and rumination. Emotional creativity and psychological flexibility were other internal factors considered as predictors.   The demographic factors which are considered can predict PTG are being female, age, and economic status. The results of this literature review found that most studies on predictors for PTG came from the geographical setting of China, with Cross-Sectional as the most preferred study design. Findings from this SLR contribute to future research agenda concerning study design and geographical setting, as well as mental health promotion to increase PTG in the community after years of COVID-19 pandemic. Keyword: Posttraumatic; growth; predictor factors, COVID-19 Pandemic.